2018
DOI: 10.1002/ange.201803649
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Giant Cerium–Bismuth Tungstate Clusters into a 3D Porous Framework with High Proton Conductivity

Abstract: The exploration of high nuclearity molecular metal oxide clusters and their reactivity is a challenge for chemistry and materials science. Herein, we report an unprecedented giant molecular cerium–bismuth tungstate superstructure formed by self‐assembly from simple metal oxide precursors in aqueous solution. The compound, {[W14CeIV6O61]([W3Bi6CeIII3(H2O)3O14][B‐α‐BiW9O33]3)2}34− was identified by single‐crystal X‐ray diffraction and features 104 metal centers, a relative molar mass of ca. 24 000 and is ca. 3.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 39 publications
(49 reference statements)
0
7
0
Order By: Relevance
“… Compared with OTTMHPOMs, exploration and investigation on OT–Ln heterometallic POMs (OTLnHPOMs) are relatively laggard because of the fact that Ln 3+ ions possess a strong oxytropic ability for highly negative POM entities, often producing amorphous sediments, which results in some difficulties in obtaining their single crystals. , Therefore, it is extremely challenging to develop suitable reaction strategies for synthesizing OTLnHPOMs. However, it is well-known that Ln-incorporated POMs are of considerable interest because of their remarkable properties in luminescence, Lewis acid catalysis, electrochemistry, and magnetism. Under this background, we began to explore this field. Through persistent efforts, very recently, our group has successfully synthesized two series of OTLnHPOMs with discrete structures by a facile synthetic method based on simple reactants in the assistance of organic solubilizers (here is dimethylamine hydrochloride), including the first OT–Ln heterometallic tellurotungstates (Figure S1e) and tetrameric S -shaped OTLnHPOMs (Figure S1f).…”
Section: Introductionmentioning
confidence: 99%
“… Compared with OTTMHPOMs, exploration and investigation on OT–Ln heterometallic POMs (OTLnHPOMs) are relatively laggard because of the fact that Ln 3+ ions possess a strong oxytropic ability for highly negative POM entities, often producing amorphous sediments, which results in some difficulties in obtaining their single crystals. , Therefore, it is extremely challenging to develop suitable reaction strategies for synthesizing OTLnHPOMs. However, it is well-known that Ln-incorporated POMs are of considerable interest because of their remarkable properties in luminescence, Lewis acid catalysis, electrochemistry, and magnetism. Under this background, we began to explore this field. Through persistent efforts, very recently, our group has successfully synthesized two series of OTLnHPOMs with discrete structures by a facile synthetic method based on simple reactants in the assistance of organic solubilizers (here is dimethylamine hydrochloride), including the first OT–Ln heterometallic tellurotungstates (Figure S1e) and tetrameric S -shaped OTLnHPOMs (Figure S1f).…”
Section: Introductionmentioning
confidence: 99%
“…have rendered new POTs a prime target in new materials design. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Due to the interesting magnetic and electronic properties of transition metals (TMs), one of the most extensive studies in new POTs design is the introduction of TMs or TM-oxo clusters into POTs for creating TM-incorporated POTs. After decades of effort, a library of TM-incorporated POTs has been synthesized and constitutes the largest subclass of POTs.…”
Section: Introductionmentioning
confidence: 99%
“…Several giant POM molecules have been synthesized using Ce as linkers of building blocks. [28][29][30][31] Furthermore, Ce-containing POMs exhibit interesting properties such as interactions with amino acids, [32,33] catalysis of protein hydrolysis, [34] catalysis for photochemical reactions, [35] and oxidation catalysis. [36] Pope et al reported the creation a Ce-encapsulated POM by reacting a Na-encapsulated Preyssler compound with cerium ammonium nitrate, (NH 4 ) 2 Ce 4 + (NO 3 ) 6 .…”
Section: Introductionmentioning
confidence: 99%